Electrochemically stable tunnel-type α-MnO2-based cathode materials for rechargeable aqueous zinc-ion batteries - De Luna, Yannis; Alsulaiti, Asma; Ahmad, Mohammad I.; Nimir, Hassan; Bensalah, Nasr (Frontiers in Chemistry, 2023)
The purpose of this study is the synthesis of α-MnO2-based cathode materials for rechargeable aqueous zinc ion batteries by hydrothermal method using KMnO4 and MnSO4 as starting materials. The aim is to improve the understanding of Zn2+ insertion/de-insertion mechanisms. The as-prepared solid compounds were characterized by spectroscopy and microscopy techniques. X-ray diffraction showed that the hydrothermal reaction forms α-MnO2 and Ce4+-inserted MnO2 structures. Raman spectroscopy confirmed the formation of α-MnO2 with hexagonal MnO2 and Ce-MnO2 structures. Scanning electron microscopy (SEM) confirmed the formation of nanostructured MnO2 (nanofibers) and Ce-MnO2 (nanorods). The electrochemical performance of MnO2 was evaluated using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) tests in half-cells. CV results showed the reversible insertion/de-insertion of Zn2+ ions in MnO2 and Ce-MnO2. GCD cycling tests of MnO2 and Ce-MnO2 at 2500 mA/g demonstrated an impressive electrochemical performance, excellent cycling stability throughout 500 cycles, and high rate capability. The excellent electrochemical performance and the good cycling stability of MnO2 and Ce-MnO2 nanostructures by simple method makes them promising cathode materials for aqueous rechargeable zinc-ion batteries.